Health Law, Constitutional Court Ruling, and Handling of Medical Services: Juridical Analysis of Constitutional Court Decision Number 111/PUU-XXII/2024 - Lili Andriani Gofar (Journal of Law and Humanities Review, 2026)
Law Number 17 of 2023 concerning Health is a fundamental change in the Indonesian health legal system because it integrates various regulations that were previously scattered in a number of sectoral laws into a more comprehensive health legal framework. The law regulates the rights and obligations of the community, the implementation of health services, medical personnel and health workers, health service facilities, supervision, and legal accountability in health services. One of the important issues after the enactment of Law Number 17 of 2023 is the regulation of Collegiums, Councils, professional independence, and the mechanism for supervision of medical and health workers. The issue was then tested through the Constitutional Court Decision Number 111/PUU-XXII/2024. This research aims to analyze the legal position of Law Number 17 of 2023, the substance of the Constitutional Court Decision Number 111/PUU-XXII/2024, and its implications for the handling of medical services and the legal protection of patients and medical personnel. The research uses a normative juridical method with a legislative approach, a conceptual approach, and a case approach. The results of the study show that the Constitutional Court Decision Number 111/PUU-XXII/2024 strengthens the principle of Collegium independence and reorganizes the relationship between Collegium, Council, government, professional organizations, and professional supervision mechanisms. The decision has important implications for legal certainty, the quality of medical services, patient protection, and the professionalism of medical personnel. Therefore, the implementation of Law Number 17 of 2023 must be placed within the framework of a balance between state authority, professional scientific independence, patient safety, and the public's right to quality health services.